Increasing Access to Special Collections - Erway, Ricky (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
In an environment where we increasingly have access to a collective collection of digitized books, special collections will become increasingly invisible if they are not accessible online. In an era of increasing expectations and decreasing budgets, finding ways to streamline some of our processes is the best way to enable us to do more with less. This report details a number of investigations into how access to special collections can be increased. It includes guidance running the gamut from digitization and rights management to policies and procedures.